2021
DOI: 10.1071/mf21179
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of visual observation and DNA metabarcoding to assess the diet of juvenile sea turtle

Abstract: The contents of the digestive tracts of 21 loggerhead turtles (20 juveniles and 1 adult) collected along the French Mediterranean coast were extracted during necropsies. Hard and soft items were collected and identified by visual observation. A 15-mL sample of the liquid from the rinsed contents of each digestive tract was collected and dietary DNA (dDNA) was extracted and amplified with a 18S universal eukaryotic primers. The obtained reads were compared with taxonomic DNA reference database. Ten taxonomic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Sea urchins were abundant in Casale et al (2008b), but were only found once in our study, probably due to the differences in substrate. Other soft-bodied prey might have remained under-detected in our analyses, as seems to be suggested by the absence of rather common species in the marine habitat, for instance Cnidarians, Annelids or sea cucumbers, known to be present in the GoM (Storelli et al 2001;De Leonardis et al 2008) and present in the diet of loggerhead turtles in other areas (Tomas et al 2001;Casale et al 2008b;Benhardouze et al 2021;Martin et al 2021;Palmer et al 2021). If turtles tend to frequent the trawled areas, the absence of some taxa could indicate depletion of benthic communities because of repeated trawling activity (Kaiser et al 2003;Handley et al 2014), i.e.…”
Section: Diet Compositionmentioning
confidence: 82%
See 1 more Smart Citation
“…Sea urchins were abundant in Casale et al (2008b), but were only found once in our study, probably due to the differences in substrate. Other soft-bodied prey might have remained under-detected in our analyses, as seems to be suggested by the absence of rather common species in the marine habitat, for instance Cnidarians, Annelids or sea cucumbers, known to be present in the GoM (Storelli et al 2001;De Leonardis et al 2008) and present in the diet of loggerhead turtles in other areas (Tomas et al 2001;Casale et al 2008b;Benhardouze et al 2021;Martin et al 2021;Palmer et al 2021). If turtles tend to frequent the trawled areas, the absence of some taxa could indicate depletion of benthic communities because of repeated trawling activity (Kaiser et al 2003;Handley et al 2014), i.e.…”
Section: Diet Compositionmentioning
confidence: 82%
“…In support of that, GEL had among the highest IRI guts . For instance, Martin et al (2021) did not find Ctenophores in gut contents but detected their presence only through DNA, supporting their fast digestion. Tomas et al (2001) found a high frequency of Thaliacea in an area that is generally considered an oceanic area for small juveniles.…”
Section: Diet Compositionmentioning
confidence: 84%
“…Though the prospect of DNA‐based quantification continues to become more attractive with advances in computational modelling (Piñol et al, 2019) and DNA amplification approaches (e.g., digital‐droplet PCR), the biases inherent to molecular techniques currently leave only a weak and imprecise relationship between prey sequence count and biomass (Lamb et al, 2019). While the present study used stable isotope analysis to overcome this prey quantification gap, researchers have supplemented DNA‐based studies with morphology‐based prey identification (Martin et al, 2021) and other chemical‐based techniques (fatty acid analysis; Génier et al, 2021) to get a better understanding of prey amounts. With that said, not all studies will have the instrumentation, personnel or financial capabilities to perform–essentially–two separate dietary studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive information that is now available on the trophic ecology of green turtles (i.e., [ 13 , 40 , 41 , 61 , 62 ]), insights on their gut microbial community composition are still scarce (but see [ 9 , 63 , 64 ]). Here, we explored the microbial community composition from four GI tract compartments of green sea turtles ( Tables S5 and S6 ) from Guinea-Bissau, and from their potential food items ( Table S7 ) using 16S rRNA metabarcoding, while, at the same time, establishing microbial baselines for the different green turtle GI compartments and the diverse food item groups.…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding has already been applied to assess sea turtle behavior [ 39 ] and diet composition [ 35 , 40 , 41 ]. Here, we assess the gut microbiome of green turtles (juveniles and hatchlings) from the Bijagós archipelago, Guinea-Bissau, by targeting the 16S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%